2021
DOI: 10.1038/s41388-021-01666-z
|View full text |Cite
|
Sign up to set email alerts
|

RBMX suppresses tumorigenicity and progression of bladder cancer by interacting with the hnRNP A1 protein to regulate PKM alternative splicing

Abstract: The prognosis for patients with metastatic bladder cancer (BCa) is poor, and it is not improved by current treatments. RNA-binding motif protein X-linked (RBMX) are involved in the regulation of the malignant progression of various tumors. However, the role of RBMX in BCa tumorigenicity and progression remains unclear. In this study, we found that RBMX was significantly downregulated in BCa tissues, especially in muscle-invasive BCa tissues. RBMX expression was negatively correlated with tumor stage, histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 62 publications
0
35
0
Order By: Relevance
“…Genes of this family have been frequently associated with cancers [ 19 , 20 , 21 ]. RBMX is a chromosome-x-linked RNA binding motif protein, which has also been associated with bladder cancer [ 22 ] and kidney cancer [ 23 ]. A good example for altered miRNA-matching 3′-UTR binding sequences is the TP53 mutation (C→T) at chromosome 17 position 7,673,780, which altered the binding sequence to miR-150-5p in TCGA’s LGG cohort.…”
Section: Resultsmentioning
confidence: 99%
“…Genes of this family have been frequently associated with cancers [ 19 , 20 , 21 ]. RBMX is a chromosome-x-linked RNA binding motif protein, which has also been associated with bladder cancer [ 22 ] and kidney cancer [ 23 ]. A good example for altered miRNA-matching 3′-UTR binding sequences is the TP53 mutation (C→T) at chromosome 17 position 7,673,780, which altered the binding sequence to miR-150-5p in TCGA’s LGG cohort.…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by different mechanisms including alternative splicing, polyadenylation and apoptosis in somatic and germ cells, and the obvious examples of genes are hnRNPG-T, CSTF2T, and BIRC8 (Elliott et al, 2000;Richter et al, 2001;Dass et al, 2002;Grozdanov et al, 2018;Bousoik et al, 2019;Zhou et al, 2019;Yan et al, 2021). RBMX protein has been implicated in splice site selection, and RBMX-derived retrogene product, hnRNPG-T, could be specialized in alternative splicing in germ cells (Elliott et al, 2000;Zhou et al, 2019;Yan et al, 2021). CSTF2T could function in the non-canonical polyadenylation of mRNAs in germ cells (Dass et al, 2002;Grozdanov et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al reported that RNA-binding motif protein X-linked (RBMX) regulated cell proliferation, colony formation, and metastatic ability in metastatic BC [ 106 ]. They observed that RBMX competitively inhibited the combination of the RGG motif in hnRNP A1 and the sequence flanking PKM exon 9, leading to the formation of lower PKM2 and higher PKM1 levels, which attenuated the tumorigenicity and progression of metastatic BC.…”
Section: Various Effects Of Glycolytic Enzymes On Phenotypes Of Ucmentioning
confidence: 99%